Smart pH- and Temperature-Sensitive Micelles Based on Chitosan Grafted with Fatty Acids to Increase the Efficiency and Selectivity of Doxorubicin and Its Adjuvant Regarding the Tumor Cells - Igor D. Zlotnikov; Dmitriy A. Streltsov; Alexander A. Ezhov; Elena V. Kudryashova (Pharmaceutics, 2023)
The main factors that determine the low effectiveness of chemotherapy are the low target bioavailability of antitumor drugs and the efflux process. In attempts to overcome this problem, several approaches are proposed here. Firstly, the development of polymeric micellar systems based on chitosan grafted by fatty acids (different types to optimize their properties), which, on the one hand, increase the solubility and bioavailability of cytostatics and, on the other hand, effectively interact with tumor cells due to the polycationic properties of chitosan, allowing for more effective penetration of cytostatic drugs into the cells. Secondly, the use of adjuvants—synergists of cytostatics (such as eugenol) included in the same micellar formulation—that selectively enhance the accumulation and retention of cytostatics in the tumor cells. pH- and temperature-sensitive polymeric micelles developed show high entrapment efficiency for both cytostatics and eugenol (EG) >60% and release the drug in a prolonged manner for 40 h in a weakly acidic medium corresponding to the microenvironment of tumors. In a slightly alkaline environment, the drug circulates longer (more than 60 h). The thermal sensitivity of micelles is realized due to an increase in the molecular mobility of chitosan, which undergoes a phase transition at 32–37 °C. The effect of the cytostatic drug doxorubicin (Dox) on cancerous A549 cells and model healthy cells of human embryonic renal epithelium (HEK293T) was studied by FTIR spectroscopy and fluorescence microscopy. Micellar Dox penetrates into cancer cells 2–3 times more efficiently when using EG adjuvant, which inhibits efflux, as demonstrated by a significant increase in the ratio of intra- and extracellular concentrations of the cytostatic. However, here it is worth remembering about healthy cells that they should not be damaged: according to changes in the FTIR and fluorescence spectra, the penetration of Dox into HEK293T when using micelles in combination with EG is reduced by 20–30% compared to a simple cytostatic. Thus, experimental developments of combined micellar cytostatic drugs have been proposed to increase the effectiveness of cancer treatment and overcome multiple drug resistance.